Enzymatic Modification of Milk Proteins for the Preparation of Low Fat Dahi. Issue 5 (15th December 2015) - Paramban Rahila, Mundakka; Kumar, Rajesh; Mann, Bimlesh; Koli, Pankaj S
Abstract: This study was conducted to evaluate the effect of transglutaminase addition on the rheological and sensory properties of low‐fat set dahi. The enzyme was added to low fat milk after preheat treatment at the rate of 5 U/g of protein for cow milk and 3 U/g of protein for buffalo milk. Once desired cross‐linkage was obtained, transglutaminase was inactivated by heat before culturing. Transglutaminase treatment resulted in improvement of the rheological and sensory properties of dahi prepared from cow or buffalo skim milk and partially skimmed milk. It improved the water‐holding capacity up to 85% in skim milk dahi and up to 90% in partially skimmed milk dahi, and firmness up to 1.1 N in cow skim milk dahi and up to 1.8 N in cow partially skimmed milk dahi; these values were almost double in low‐fat buffalo milk dahi. Syneresis, appearance and consistency of the final product were also improved. The high gel strength improved the storage stability of treated dahi at refrigerated temperature up to 2 weeks. Practical Applications: Dahi is the most important fermented milk product used in India from time immemorial. In Indian system of medicine (Ayurveda), dahi has been strongly recommended for curing ailments like dyspepsia, dysentery and other gastrointestinal disorders. This product is also believed to improve appetite and vitality. Dahi is a very nourishing food. It is available as source of protein, essential vitamins and minerals. It is also a rich source of calcium and riboflavin. We consider the low fat dahi, which provides all the benefits of Dahi without the bad effects of milk fat. As the reduction of fat from milk affects the quality of dahi such as viscosity, gelation, water‐holding capacity, etc. Through this study, it was observed that the application of transglutaminase pretreatment is a promising alternative to improve textural properties of low fat dahi. Enzymatic cross‐linking of milk proteins results in specific changes in product microstructure; this helps to produce good quality dahi from skim milk or partially skimmed milk.